Postprandial glucose, insulin and incretin responses differ by test meal macronutrient ingestion sequence (pattern study) - Sun, Lijuan (2020)
Background: Previous studies have shown that the sequential order of consuming different food components significantly impacts postprandial glucose and insulin excursions in prediabetes and type 2 diabetes, but the causative mechanisms in healthy humans remain ill-defined. Objective: Using a typical Asian meal comprising vegetables, protein (chicken breast), and carbohydrate (white rice), the aim of this study was to examine the effect of food intake sequence on postprandial glucose, insulin and incretin secretions in healthy adults. Design: Sixteen healthy Chinese adults participated in a randomized, controlled, crossover meal trial. Subjects consumed in random order 5 experimental isocaloric meals that differed in the food intake sequence of vegetables, protein and carbohydrate. Glucose, insulin, incretins and satiety markers were measured over 3 h. Results: There were significant food intake sequence × time interaction effects on plasma glucose, insulin, glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide-1 (GLP-1) concentrations (P < 0.001). In comparison with rice consumed first followed by vegetable and meat (R-VM), the overall postprandial glucose response was significantly attenuated after the food intake sequence of vegetable first, followed by meat and rice (V-MR) or meat first, followed by vegetable and rice (M-VR) or vegetable first followed by meat and rice (V-M-R) or vegetable, meat and rice consumed together (VMR). The insulin iAUC (0–60) was significant lower after V-M-R than M-VR, VMR and R-VM. V-M-R food intake sequence stimulated higher GLP-1 release than other meal sequences. However, GIP response was lower after V-MR and V-M-R than M-VR and R-MR food intake sequences. Conclusions: Food macronutrient intake sequence can considerably influence its glycemic, insulinemic and incretin responses. V-M-R food intake sequence attenuates the glycemic response to a greater degree with accentuated GLP-1 stimulation without any increased demand for insulin. The sequence of food intake has great potential as a novel and simple behavioral strategy to modulate glycemic response in healthy adults.